Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Hasil Belajar Siswa di Nida Suksasat Islamic Priciple School - Nurani Atika Putri Lubis; Amin Basri; Suci Perwita Sari (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Learning outcomes are the most important part of the learning process. The aim of this research is to determine the effect of the Make A Match learning method on elementary school students' learning outcomes. This type of research is Quantitative research with True Experimental Design. The design used in this research was Pretest-posttest Control Group Design. Sampling was carried out using random sampling technique. Data collected uses observation, tests and documentation, while research data is analyzed using descriptive statistics and inferential statistics. The research results show that this learning model influences the learning outcomes of elementary school students. The application of the Cooperative Learning Model Make A Match is higher than the pretest average. The existence of game elements in the Make A Match learning model prevents students from getting bored and stiff in the learning process because students learn while playing. Game elements in this lesson include finding pairs of question cards and answer cards held. Thus, the make a match model is an important part of improving student learning outcomes and is a varied method of choice for teachers.